The Influence of BOPO, LDR/LFR, and NPL on the Profitability of Core Capital Bank Group (KBMI) 1 Banks During the Covid-19 Pandemic - Sutardiyanta, Ihwan; Nugraha, Nugraha (Badan Penerbit Fakultas Ekonomi dan Bisnis Universitas Singaperbangsa Karawang, 2024)
This study aims to evaluate the impact of the Operational Costs to Operating Income ratio (BOPO), Loan to Deposit Ratio (LDR), and Non-Performing Loans (NPL) on Profitability, measured through the Return On Assets (ROA) and Net Profit Margin (NPM) ratios of Bank KBMI 1 during the Covid-19 pandemic period spanning from 2020 to 2023. The research encompassed 28 companies affiliated with Bank KBMI 1/BUKU 1 as the population, and 25 companies were chosen as samples using purposive sampling techniques. The analysis was conducted through multiple linear regression on a dataset comprising 75 time series. The findings of the research indicate that: (1) BOPO exhibits a negative and statistically significant influence on profitability, encompassing both ROA and NPM, (2) NPL and LDR/LFR do not wield a significant impact on profitability, be it ROA or NPM. Consequently, in totality, BOPO, LDR/LFR, and NPL collectively contribute to influencing profitability.